1995
DOI: 10.1073/pnas.92.3.689
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic mice expressing an altered murine superoxide dismutase gene provide an animal model of amyotrophic lateral sclerosis.

Abstract: Amyotrophic lateral sclerosis is a progres- (5) to propose that it is a dearth of activity that leads to the neurodegenerative syndrome.Studies of humans with ALS are complicated by the lack of genetic homogeneity or environmental uniformity. Moreover, possible early signs of disease that might appear prior to overt symptoms and could allow preemptive medical intervention are difficult to identify. For these reasons, it is highly desirable to develop an animal model of FALS. The transgenic mouse system (6-8) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
341
1
5

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 643 publications
(358 citation statements)
references
References 20 publications
10
341
1
5
Order By: Relevance
“…This model recapitulates most relevant clinical and histopathological features of both familial and sporadic forms of the human disease [3]. It is also of relevance that alterations of the SOD1 protein have been reported in sporadic ALS patients [4], increasing the interest of this murine model.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…This model recapitulates most relevant clinical and histopathological features of both familial and sporadic forms of the human disease [3]. It is also of relevance that alterations of the SOD1 protein have been reported in sporadic ALS patients [4], increasing the interest of this murine model.…”
Section: Introductionmentioning
confidence: 72%
“…expresses the human mutated form of the SOD1 gene with a glycine to alanine conversion at the 93rd codon [3]. This model recapitulates most relevant clinical and histopathological features of both familial and sporadic forms of the human disease [3].…”
Section: Introductionmentioning
confidence: 87%
“…Based on these genetic mutations, transgenic animal models have been developed for the study of ALS. The most widely used model is a transgenic mouse with a glycine-to-alanine conversion at the 93rd codon of the SOD1 gene in high copy number (SOD1 G93A ) [3]. The phenotype of this mice recapitulates several clinical and histopathological features of both familial and sporadic forms of the human disease [3].…”
Section: Introductionmentioning
confidence: 99%
“…The most widely used model is a transgenic mouse with a glycine-to-alanine conversion at the 93rd codon of the SOD1 gene in high copy number (SOD1 G93A ) [3]. The phenotype of this mice recapitulates several clinical and histopathological features of both familial and sporadic forms of the human disease [3]. Moreover, it has been recently reported that alterations of the SOD1 protein are also related to sporadic ALS cases [4], increasing the interest in the study of transgenic animals.…”
Section: Introductionmentioning
confidence: 99%
“…The line of SOD1 transgenic mice containing an amino acid substitution of glycine at position 93 by alanine (G93A) has been reported to become paralyzed in one or more limbs due to loss of motor neurons from the spinal cord, with these mice dying by 4 to 5 months of age. 4,5 Pathologic changes with vacuolar formation in the anterior horns of the spinal cord and in selected brainstem nuclei have been seen as early as less than 3 month at a pre-clinical stage. 6 Although the mechanisms by which ALS leads to motor neuron degeneration remain unclear, they are suggested to be associated with a deficiency of neurotrophic factors, excessive excitatory amino acids, excessive oxidative stress, and promoted apoptosis.…”
Section: Introductionmentioning
confidence: 99%